Modification of an Amidolytic Heparin Assay to Express Protein-Bound Heparin and to Correct for the Effect of Antithrombin III Concentration - Lyon, Sandra G; Lasser, Elliott C; Stein, Rosalyn (Thrombosis and Haemostasis, 1987)
A modification of an anti-Xa assay for plasma heparin has been devised using a low molecular weight dextran sulfate that competitively binds protein heparin neutralizers and displaces masked heparin. The addition of 0.12 mg dextran sulfate per ml of plasma permits heparin, neutralized by the products of platelet aggregation, to recover full functional activity against Xa. The assay will permit a more accurate assessment of both exogenous plasma heparin and endogenous liepaiin-like activity in blood samples collected with varying techniques. A further modification is proposed employing polybrene to neutralize the plasma heparin-like material providing a concurrent control for each sample that increases accuracy by eliminating the effect of varying AT-III levels which have anti-Xa activity.
Keywords: Heparin; Antithrombin III; Dextran sulfate; Polybrene